The Location of Sales Offices and the Attraction of Cities - Holmes, Thomas J. (Journal of Political Economy, 2005)
This paper examines how manufacturers locate sales offices across cities. Sales office costs are assumed to have four components: a fixed cost, a frictional cost for out‐of‐town sales, a cost‐reducing knowledge spillover related to city size, and an idiosyncratic match quality for each firm‐city pair. A simple theoretical model is developed and is estimated using data from the Census of Wholesale Trade. The factors emphasized in the home market effect literature, namely, fixed costs and frictional costs, are found to play an important role in location decisions. Match quality also matters. The results for knowledge spillovers are mixed.